The association between ischaemia-modified albumin levels in umbilical vein and intrauterine growth restriction. (January 2015) - Karadeniz, O.; Mendilcioglu, I.; Ozdem, S.; Ozekinci, M.; Sanhal, C. Y.; Uzun, G.; Sakinci, M.; Simsek, M.
Abstract Intrauterine growth restriction (IUGR) is one of the most common problems in obstetrics. Ischaemia-modified albumin (IMA), a product deriving from albumin as a result of the modification by oxidative free radicals in response to hypoxia, was previously used as a marker of ischaemia in acute coronary syndrome. We performed this study to determine whether umbilical venous IMA levels are associated with IUGR. A total of 40 pregnancies with IUGR were compared with 40 of normal fetal development. Blood samples were obtained from the umbilical vein after delivery. IMA levels in the IUGR group were higher than in the control group (78.74 ± 6.87 vs 74.43 ± 7.84 U/ml, respectively, p = 0.011). An elevated IMA level was associated with IUGR (OR: 1.079, 95% CI: 1.000–1.163, p = 0.049). We suggest that IMA, which was formerly proved to arise in ischaemic conditions, may also be a valuable marker in perinatal hypoxia and IUGR detection.